2014
DOI: 10.1093/mutage/geu029
|View full text |Cite
|
Sign up to set email alerts
|

Aroclor 1254-induced genotoxicity in male gonads through oxidatively damaged DNA and inhibition of DNA repair gene expression

Abstract: The present study aimed to examine if multiple exposure to Aroclor 1254, a commercial mixture of polychlorinated biphenyls, had any genotoxic potential on gonads of male mice; moreover, the molecular mechanism(s) underlying this deleterious effects were elucidated. In the standard comet assay, there were significant increases in the incidence of DNA strand breaks in sperm of mice killed after 3 and 24h of last treatment with 4 mg/kg/day Aroclor 1254 for 5 weeks, while no significant difference in the DNA stran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Excessive intracellular ROS production is well known to attack bases in nucleic acids, amino acid side chains in proteins and double bonds in unsaturated fatty acids which eventually leads to DNA, RNA, proteins and lipids damage (Wu et al ., ; Fedato & Maistro, ; Patlolla et al ., ). Moreover, oxidative damage to DNA has been suggested to be one of the most important factors responsible for PCBs‐induced gonadal cell genotoxicity and carcinogenic modes of action (Attia et al ., ). However, co‐treatment of quercetin with PCBs significantly ameliorated the fragmentation of DNA in the treated rats.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Excessive intracellular ROS production is well known to attack bases in nucleic acids, amino acid side chains in proteins and double bonds in unsaturated fatty acids which eventually leads to DNA, RNA, proteins and lipids damage (Wu et al ., ; Fedato & Maistro, ; Patlolla et al ., ). Moreover, oxidative damage to DNA has been suggested to be one of the most important factors responsible for PCBs‐induced gonadal cell genotoxicity and carcinogenic modes of action (Attia et al ., ). However, co‐treatment of quercetin with PCBs significantly ameliorated the fragmentation of DNA in the treated rats.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, PCBs are well reported to exert their toxic effects by increasing free radicals generation, thus inducing oxidative stress (Murgesan et al ., ; Aly et al ., ; Atessahin et al ., ; Aly, ). Recent studies on PCBs toxicity demonstrated that PCB‐induced genotoxicity in male gonads through DNA oxidative damage and inhibition of DNA repair gene expression (Attia et al ., ). Increased ROS production in the cellular environment can damage DNA and oxidise cellular proteins (Patlolla et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…As sperm has a highly limited cytosolic antioxidants and limited base exicision repair mechanisms by virtue of it being transcriptionally and translationally inert, the DNA damage borne in sperm DNA persists (Attia et al, 2014). DOI:http://dx.doi.org/10.7314/APJCP.2015.16.16.6967 Tobacco Use Increases Oxidative DNA Damage in Sperm -Possible Etiology of Childhood Cancer A study from our lab documented that significantly lower levels of PARP1 and OGG1 in mature sperm of infertile men Thilagavathi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although ROS is required for physiological processes (Haque et al 2014), the abnormal accumulation thereof can lead to DNA strand breaks, peroxidation of unsaturated lipids, disruption of mitochondrial function, and oxidative damage to DNA (Fullston et al 2017;Roychoudhury et al 2017). Spermatozoa are vulnerable to ROS due to the presence of limited cytoplasmic antioxidants and limited repair mechanisms (Attia et al 2014). Due to the translational and transcriptional inert nature of DNA, the DNA damage borne in sperm DNA persists (Attia et al 2014).…”
Section: Mechanisms Through Which Tobacco Smoke Affects Male Fertilitymentioning
confidence: 99%